If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.3x + -0.5x + 3 = -4 Reorder the terms: 3 + 0.3x + -0.5x = -4 Combine like terms: 0.3x + -0.5x = -0.2x 3 + -0.2x = -4 Solving 3 + -0.2x = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -0.2x = -4 + -3 Combine like terms: 3 + -3 = 0 0 + -0.2x = -4 + -3 -0.2x = -4 + -3 Combine like terms: -4 + -3 = -7 -0.2x = -7 Divide each side by '-0.2'. x = 35 Simplifying x = 35
| -4x-5x= | | 9n-34=6n+5 | | m+(-5)=19 | | 5(x+4)=6(3x-2) | | 4y+xy=11 | | .75a+14=8 | | 2(1-2b)+2(1+5b)=-9+6b | | (x^4)+(41x^2)+400=0 | | 6p+(p-4)=4p | | 264-3x=42x+19 | | -36x^4+25x^3-4= | | h+(-9)=-9 | | (x^4)+(4x^2)+400=0 | | 15t+9=5t+9 | | 5b-12=14 | | 9(x-4)=72 | | -10y-7=6y+9 | | d-15=44 | | -441=4(-8n-4) | | 2(8x+2)=3(2x-7) | | 5x+2x=6x-2 | | 5x-6(3x+4)=9(x-6)+3 | | -9x+4x+15-10x= | | 7u^2-48u-7=0 | | 0.02-0.02(x+2)=-0.04(2-x) | | 6x+6=4x+2 | | 4-(3.5x+2)=x-7 | | 10y-7-6y+9= | | 125x^3-8= | | -10y-7-6y+9= | | 5[15x+25]=950 | | 3x^2-4x-9=0 |